Do Geographic Region, Pathologic Chronicity, and Hospital Affiliation Affect Access to Care Among Medicaid- and Privately-Insured Foot and Ankle Surgery Patients?. Issue 4 (22nd October 2020) - Pitts, Charles C.; McKissack, Haley M.; He, Jun Kit; Alexander, Bradley; Sutherland, Charles R.; Cage, Benjamin B.; Shah, Ashish
Category: Other Introduction/Purpose: Studies have shown that patients enrolled in Medicaid have difficulty obtaining access to care compared to patients with private insurance. Whether variables such as geographic location, state expansion vs. non-expansion, and private versus academic affiliation affect access to care among foot and ankle surgery patients enrolled in Medicaid has not been previously established. Methods: Twenty providers from each of five Medicaid-expanded and five non-expanded states in different U.S. geographic regions were randomly chosen via the American Orthopaedic Foot & Ankle Society (AOFAS) directory. One investigator contacted each office requesting the earliest available appointment for their fictitious relative's acute Achilles tendon rupture or hallux valgus. Investigator insurance was stated to be Medicaid for half of phone calls, and Blue-Cross Blue-Shield (BCBS) for the other half. Appointment success rate and average time to appointment were compared between private insurance and Medicaid. Results were further compared across geographic regions, between private and academic practices, and between urgent acute injury (Achilles rupture) and chronic non-urgent injury (hallux valgus). Results: Appointments were successful for all 100 (100%) calls made with BCBS, in comparison to 73 of 100 calls (73%) with Medicaid (p<0.001). Both acute and chronic injury had significantly higher success rates with BCBS than Medicaid (p<0.001). Appointment success rate was significantly lower with Medicaid than with BCBS (p<=0.01) in all geographic regions. Success rate with Medicaid (66.7%) was significantly lower than with BCBS (100.0%, p<0.001) for private practice offices, but not for academic practices. Conclusion: Patients with Medicaid experience difficulty in obtaining appointments for common non-emergent foot and ankle problems and may experience increased difficulty scheduling appointments at private rather than academic institutions. The medical community should continue to seek and identify potential interventions which can improve access to orthopaedic care for all patients, regardless of insurance status.